Inclusive access to emergency services: A complete system focused on hearing-impaired citizens - Constantinou, Vaso (My University, 2017)
In case of emergency, hearing impaired people are not always able to access emergency services and, hence, they do not have equal access to social support and infrastructure. In this work, we undertake the development and evaluation of a system aiming to meet the communication needs of hearing impaired citizens in cases of emergency. The system consists of (i) a mobile application that records and sends the details of an emergency event, and (ii) a central management system that handles these calls from the operation center at the emergency services. The system was completed in four cycles of design, development and evaluation with the involvement of 74 hearing impaired users and three officers from the Cyprus Police (Emergency Response Unit).
Keywords: Action research; Emergency services; Inclusive citizen participation; Inclusive design; Technology for hearing impaired people